DNA methylation and exposure to ambient air pollution in two prospective cohorts. (November 2017) - Plusquin, Michelle; Guida, Florence; Polidoro, Silvia; Vermeulen, Roel; Raaschou-Nielsen, Ole; Campanella, Gianluca; Hoek, Gerard; Kyrtopoulos, Soterios A.; Georgiadis, Panagiotis; Naccarati, Alessio; Sacerdote, Carlotta; Krogh, Vittorio; et al.
Abstract: Long-term exposure to air pollution has been associated with several adverse health effects including cardiovascular, respiratory diseases and cancers. However, underlying molecular alterations remain to be further investigated. The aim of this study is to investigate the effects of long-term exposure to air pollutants on (a) average DNA methylation at functional regions and, (b) individual differentially methylated CpG sites. An assumption is that omic measurements, including the methylome, are more sensitive to low doses than hard health outcomes. This study included blood-derived DNA methylation (Illumina-HM450 methylation) for 454 Italian and 159 Dutch participants from the European Prospective Investigation into Cancer and Nutrition (EPIC). Long-term air pollution exposure levels, including NO2, NOx, PM2.5, PMcoarse, PM10, PM2.5 absorbance (soot) were estimated using models developed within the ESCAPE project, and back-extrapolated to the time of sampling when possible. We meta-analysed the associations between the air pollutants and global DNA methylation, methylation in functional regions and epigenome-wide methylation. CpG sites found differentially methylated with air pollution were further investigated for functional interpretation in an independent population (EnviroGenoMarkers project), where (N = 613) participants had both methylation and gene expression data available. Exposure to NO2 was associated with a significant global somatic hypomethylation (p-value = 0.014). Hypomethylation of CpG island's shores and shelves and gene bodies was significantly associated with higher exposures to NO2 and NOx . Meta-analysing the epigenome-wide findings of the 2 cohorts did not show genome-wide significant associations at single CpG site level. However, several significant CpG were found if the analyses were separated by countries. By regressing gene expression levels against methylation levels of the exposure-related CpG sites, we identified several significant CpG-transcript pairs and highlighted 5 enriched pathways for NO2 and 9 for NOx mainly related to the immune system and its regulation. Our findings support results on global hypomethylation associated with air pollution, and suggest that the shores and shelves of CpG islands and gene bodies are mostly affected by higher exposure to NO2 and NOx . Functional differences in the immune system were suggested by transcriptome analyses. Highlights: We studied the effects of long-term exposure to air pollutants on DNA methylation. A consistent global hypomethylation was observed for exposure to ambient NO2 and NOx . This hypomethylation was observed for CpG island's shores, shelves and gene bodies. No CpG sites were epigenome-wide significant in a combined analysis of a low and high exposed cohort.